Heavy metals in cincalok at Tanjong Kling and Umbai, Melaka / Farah Ayuni Shafie ... [et al.] - Abu Bakar, Saleha; Mohd Shahid, Nadiatul Syima; Rajan, Shantakumari; Mohd Yatim, Siti Rohana; Megat Mokhtar, Megat Azman; Shafie, Farah Ayuni (Faculty of Health Sciences, Universiti Teknologi MARA, 2019)
Heavy metal contamination becomes crucial as it can bio-magnified in human body. This study has been carried out to determine the concentration of heavy metals (lead, cadmium and copper) in cincalok samples collected from two different sources and its potential health risk. This cross sectional study was carried out to determine the concentration of heavy metals in cincalok and its relation to anthropogenic activities in Malacca Straits. Cincalok samples were collected from Tanjong Kling and Umbai, Melaka. Stratified random sampling was applied during sampling which was the samples from the same batch only. Then, the samples were treated based on US EPA method 3050 B for Acid Digestion of sediments, sludges and soils. The samples were then analyzed using the Atomic Absorption Spectrophotometer (AAS, Pin AAcle 900 Perkin Elmer) to determine the concentration of heavy metals in cincalok. The analysis showed the highest level of Copper in cincalok from both sources, small amount of cadmium and no detection of lead were shown in all samples. The sequence of order of the heavy metals measured is Cu>Cd>Pb. The Target Hazard Quotient (THQ) was low for all heavy metals and shows no potential health risk. There is significant difference for concentration of copper in cincalok from both sources. The level of heavy metals Pb, Cd and Cu did not exceed permissible limits by Malaysian Food Act 1983. Consumption of cincalok from both sources can be concluded safe as the level of selected heavy metals did not exceed the acceptable food standard limits and with low THQ level.